The Influence of Motivation on the Performance of SOPS MAKO KOARMADA II Employees - Radiansyah, Angga (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to determine the effect of work motivation on employee performance at SOPS MAKO KOARMADA II. The sample was from the population of SOPS Koarmada II employees, totaling 48 people using saturated sampling techniques. Our main data was obtained through surveys using Google Forms as a research instrument, while secondary data refers to data collected for purposes other than solving the problem under study. Our data analysis was performed using the SPSS software, which involved a normality test and then followed by a paired T-Test. The results of the normality test obtained a p value > 0.00, which indicates that the data is normally distributed. Paired T-Test obtained a Sig value of 0.000, this value is <0.05. This proves that there is a significant influence of motivation on employee performance. Recommendations based on the results of this study that it is necessary to give gifts and punishments to attract employees in increasing work motivation. Prizes are usually in the form of increasing the employee's career path and/or can be in the form of providing additional salary bonuses.